Period Poverty: An added poverty in humanitarian crisis - Dr Inayat Thaver,; Mariam Ashraf, (Journal of the Pakistan Medical Association, 2023)
The term 'period poverty' is broadly used, indicating an individual's need for menstrual products without sufficient funds to purchase them (1). Period poverty is defined as “a lack of access to menstrual products”. More than half of the world's population are menstruating people; therefore in a situation specifically during a humanitarian crisis, high-period poverty becomes challenging (2). Period poverty, like other types of poverty, is a worldwide issue and it is frequently used when people are unable to access menstrual products due to their low socioeconomic level. These items could include sanitary napkins, inner garments, and other hygiene items. It can significantly impact an individual's life, but the stigma surrounding periods poses a greater threat to women's health because it discourages people from discussing it. Several factors, including hygiene facilities, waste management, and education, pose physical, mental, and emotional challenges for numerous women. More than half of the world's population menstruates; therefore, high-period poverty becomes a challenge, especially during humanitarian crises (2). It is usually observed that adolescents and young women are frequently underrepresented populations in humanitarian settings, particularly in times of conflict like forced displacement, armed conflict, or natural catastrophes. Wherever a disaster strikes, search and rescue teams prioritize helping those evacuated to shelters and supporting efforts to provide basic necessities like food and water. As a result, other urgent needs of displaced populations, particularly displaced girls and women, may be overlooked (4). It has been observed from the global humanitarian crises, that menstruation and hygiene products such as wipes, soaps, and other menstrual products were the most important things they needed at that time (5). During the recent floods (June- Aug 2022) in Pakistan, over 33 million people were affected, and over 6.4 million required humanitarian assistance. Approximately 634 thousand people were compelled to reside in camps. Access to healthcare facilities, personnel, and essential medications and medical supplies was restricted (6)More than eight million women of reproductive age affected by floods took extreme measures to manage their periods, such as one woman who described how she had to use tree leaves during her period. (7). Post-disaster relief and rehabilitation operations rarely prioritize the menstrual hygiene needs of women. Nonetheless, there is a growing awareness of the importance of integrating comprehensive, participatory, and gender-sensitive approaches into response programs with a focus on meeting the needs of women (8). ---Continue